Oxford handbook of respiratory medicine. - Chapman, Stephen; Robinson, Grace; Stradling, John R.; West, Sophie; Wrightson, John ([Oxford] : Oxford University Press, 2014)
Respiratory ailments are the most common reason for emergency admission to hospital, the most common reason to visit the GP, and cost the NHS more than any other disease area. This pocket-sized handbook allows instant access to a wealth of information needed in the day-to-day practice of respiratory medicine.
This edition previously issued in print: 2014.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on August 18, 2016).
Keywords: Respiratory organs -- Diseases